Simultaneous estimation of Esomeprazole and Tadalafil in pharmaceutical formulations using High Performance Liquid Chromatography - Mohammed Hamad, Ahmed Al-Sharqawi, Wael Abu Dayyih, Eyad Mallah, Tawfiq Arafat (Journal of Applied Pharmaceutical Science, 2016)
An easily, specific, precise, and accurate reversed-phase HPLC method was developed and validated for simultaneous estimation of esomeprazole ( Nexium®) and tadalafil (Cialis®) in pharmaceutical formulation. The separation was achieved by using Hypersil BDS C18 column (250 mm × 4.6 mm; 5.0 μm) and acetonitrile: 0.05 M potassium dihydrogen phosphate buffer at pH 6 adjusted with phosphoric acid as a mobile phase at a flow rate of 1 mL/min. Detection was carried out at wavelength 285nm. The retention time of esomeprazole and tadalafil were 3.1, 3.7 min, respectively. The linearity was established over the concentration ranges of 60-180μg/mL and 40-120μg/mL with correlation coefficients 0.9998 and 0.9996 for esomeprazole and tadalafil, respectively. The mean recoveries were found to be in the ranges of 98–102% for esomeprazole and tadalafil. The proposed method has been validated as per ICH guidelines and successfully applied to the simultaneous estimation of esomeprazole and tadalafil in pharmaceutical formulation.
Keywords: Esomeprazole, HPLC, Tadalafil, Validation, pharmaceutical formulation.